2017
DOI: 10.3389/fonc.2017.00253
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Protective Activity of Tumor-Specific Epitopes Engineered in Bacterial Outer Membrane Vesicles

Abstract: IntroductionBacterial outer membrane vesicles (OMVs) are naturally produced by all Gram-negative bacteria and, thanks to their plasticity and unique adjuvanticity, are emerging as an attractive vaccine platform. To test the applicability of OMVs in cancer immunotherapy, we decorated them with either one or two protective epitopes present in the B16F10EGFRvIII cell line and tested the protective activity of OMV immunization in C57BL/6 mice challenged with B16F10EGFRvIII.Materials and methodsThe 14 amino acid B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 33 publications
(41 reference statements)
0
57
0
Order By: Relevance
“…A vaccine based on EGFRvIII peptide was tested in glioblastoma patients, with promising results even though EGFRvIII-negative tumor cells ultimately escaped vaccine-induced protection ( 27 ). We previously demonstrated that OMVs decorated with EGFRvIII peptide elicited specific antibodies which could inhibit the growth of a B16F10 cell line derivative expressing EGFRvIII in syngeneic C57bl6 mice ( 24 ). Since EGFRvIII-B16F10 cells, like their progenitor B16F10, express mD8-FAT1 on their surface (Figure 4A ), we tested whether the combination of mD8-FAT1-OMVs and EGFRvIII-OMVs could further enhance the anti-tumor activity of EGFRvIII-OMVs immunization in mice challenged with EGFRvIII-B16F10.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A vaccine based on EGFRvIII peptide was tested in glioblastoma patients, with promising results even though EGFRvIII-negative tumor cells ultimately escaped vaccine-induced protection ( 27 ). We previously demonstrated that OMVs decorated with EGFRvIII peptide elicited specific antibodies which could inhibit the growth of a B16F10 cell line derivative expressing EGFRvIII in syngeneic C57bl6 mice ( 24 ). Since EGFRvIII-B16F10 cells, like their progenitor B16F10, express mD8-FAT1 on their surface (Figure 4A ), we tested whether the combination of mD8-FAT1-OMVs and EGFRvIII-OMVs could further enhance the anti-tumor activity of EGFRvIII-OMVs immunization in mice challenged with EGFRvIII-B16F10.…”
Section: Resultsmentioning
confidence: 99%
“…The construction of pET-Nm-fHbp-vIII plasmid expressing the Neisseria meningitidis FHbp fused to three repeated copies of EGFRvIII peptide was previously described ( 24 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recent experiment decked OMVs with tumor antigens that elicited protective anti-tumor responses in immune-competent mice. The engineered OMVs offered synergistic protective activity, resulting in OMV platform that was particularly attractive for cancer immunotherapy (Grandi et al, 2017 ).…”
Section: A Novel Vaccine Adjuvant: Omvsmentioning
confidence: 99%
“…Bacterial strains can be engineered not only to modulate LPS endotoxicity but also to increase the blebbing, 4,[13][14][15] overexpress key target antigens, 16 and simultaneously express multiple variants or heterologous antigens (either proteins or polysaccharides). 17,18 This enabled to produce and test, to date mainly at preclinical level, several engineered OMVs carrying either bacterial, 19 viral, 20 parasitic, 21 and even cancer 22 antigens. Finally, the development of ad hoc industrial production, purification, and characterization processes has allowed to obtain well-defined and stable vaccine products in high yield and at low costs.…”
Section: Omvs As Vaccine Platformsmentioning
confidence: 99%